Husband's Support is Related to Anxiety Levels in Third Trimester Pregnant Women - Nuraeni, Eliana; Arni Nur Rahmawati; Ririn Isma Sundari (Journal Keperawatan, 2025)
Background: The pregnancy process is something that is awaited by every couple but is not free from various psychological challenges, one of which is anxiety in pregnant women. Husband's support is one of the important factors that can determine the level of anxiety of pregnant women, especially in the third trimester. Emotional, instrumental, and informational support from the husband can provide a sense of security and comfort to pregnant women. Purpose: To determine the relationship between husband's support and anxiety in pregnant women in the third trimester. Methods: This study uses quantitative research with correlational methods through a cross-sectional approach. The research location is at Posyandu, Samudra Kulon Village, Gumelar District, Banyumas Regency with a sample of 62 parents and toddlers aged 3-5 years taken using Purposive Sampling. Data collection was carried out using the Developmental Pre-Screening Questionnaire (KPSP) consisting of 9-10 questions and the Parenting Styles and Dimensions Questionnaire - Short Version (PSDQ) consisting of 32 questions. Data analysis used the Spearman rank test. Results: There is a significant and strong relationship between husband support and anxiety in third trimester pregnant mothers with a significance value of p value < 0.05 with a correlation coefficient value of r = -691. Conclusion: There is a positive correlation between parenting patterns and the development of toddlers aged 3-5 years. The better the parenting patterns applied by parents, the more optimal the development of the child.